Combined high-resolution magnetic resonance imaging and histological examination to explore the role of ligaments and tendons in the phenotypic expression of early hand osteoarthritis. Issue 10 (20th April 2006) - Tan, A L; Toumi, H; Benjamin, M; Grainger, A J; Tanner, S F; Emery, P; McGonagle, D
Abstract : Background: The pathogenesis of the early stages of hand osteoarthritis is poorly understood, but recent high-resolution magnetic resonance imaging (hrMRI) studies suggest that the joint ligaments have a major role in the phenotypic expression of the disease. Objective: To combine hrMRI and cadaveric histological studies to better understand the mechanisms of damage, and especially the role of joint ligaments and tendons in disease expression. Methods: hrMRI was carried out in the distal interphalangeal (DIP) and proximal interphalangeal (PIP) joints in 20 patients with osteoarthritis, with a disease duration ⩽12 months. Histological sections of the DIP and PIP joints were obtained from three dissecting-room specimens for comparative analysis. Results: The collateral ligaments influenced the location of both hrMRI-determined bone oedema and bone erosion in early osteoarthritis. These changes were best understood in relation to the enthesis organ concept, whereby the interaction between ligament fibrocartilages leads to bone disease. Normal ligaments were commonly associated with microdamage at insertions corresponding to ligament thickening noted in early osteoarthritis. The ligaments also influenced the location of node formation in early osteoarthritis. The DIP extensor tendon insertions were associated with the development of a neoarticular surface. Conclusions: Small-joint collateral ligaments and tendons have a central role in the early stages of hand osteoarthritis, and determine the early expression of both the soft tissue and bony changes in disease.